Projections and parameters of social capital - Dedolko, Julia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article explores the types of scientific rationality in V. S. Stepin’s classification and their specificity in social science and researches on social capital. The main trends of social dynamics and transformation of contemporary society’s social capital were characterised. The goal of the article was to identify the status of the social capital concept on socio-humanitarian knowledge on the post-non-classical stage of scientific development.
Keywords: science; scientific rationality; social-humanitarian knowledge; society; social capital